2015
DOI: 10.1136/bmjqs-2015-004269
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of HIV treatment as prevention strategy in 17 Canadian sites: immediate and sustained outcomes from a 35-month Quality Improvement Collaborative

Abstract: This study shows evidence of sustained improvements in HIV care processes and treatment outcomes for an estimated population of 2296 HIV patients in 17 BC sites. Overall success points to opportunities for other high-income countries seeking to improve HIV health outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
(27 reference statements)
1
12
0
Order By: Relevance
“…Beyond scaling up HIV testing and care sites, provincial partners sought to improve the quality of care itself through a provincial collaborative launched in 2011 that brought together 17 teams across the province to engage in continuous quality improvement and adult learning activities(#111). This collaborative later (2013) morphed into the HIV quality improvement network, mandated to address gaps in the provincial cascade of HIV care [85].…”
Section: Communitymentioning
confidence: 99%
“…Beyond scaling up HIV testing and care sites, provincial partners sought to improve the quality of care itself through a provincial collaborative launched in 2011 that brought together 17 teams across the province to engage in continuous quality improvement and adult learning activities(#111). This collaborative later (2013) morphed into the HIV quality improvement network, mandated to address gaps in the provincial cascade of HIV care [85].…”
Section: Communitymentioning
confidence: 99%
“…At the trial level, without these further analyses, the degree to which each hospital had implemented the care pathway as intended or improved would have remained unclear, as each hospital’s signal was obscured within the results of a large and heterogeneous cohort. The use of run charts to evaluate QI programmes at scale remains rare, with some notable exceptions,37 yet they are ideally suited to this level of granular data analysis. The main strength of this analysis is that we have tested this approach experientially, alongside our main trial analyses, using the same dataset, and found it was largely congruent with, but added value to, our previous understanding of what happened during the EPOCH trial.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence in support of QI interventions to improve HIV treatment services comes from places such as Canada and Ethiopia where systems-level approaches have been taken to improve health service delivery [16, 17]. …”
Section: Methodsmentioning
confidence: 99%